MENGUJI KEABSAHAN DATA PENELITIAN KUALITATIF - Riski Rahayu; Sulastri Rini Rindrayani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Data is an important thing that must be present in both qualitative and quantitative research. Collecting data and then processing it is a difficult job. Because if the data obtained is not suitable, then the research results are also not suitable, testing the validity of data is important in the research process. This paper is made to understand how to test the validity of data in qualitative research. The approach used is literature study with data collection techniques in the form of scientific articles from google schooler and other reference books related to the discussion of this paper, the analysis technique used is to process the collected data, present the data and draw conclusions at the end. From the results of this study, it can be explained that the process of testing the validity of data in qualitative research has four stages, namely: credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity).